Konsep Belas Kasih dan Nasihat dalam Menuntut Ilmu: (Studi Analisis Qs. At-Thaha Ayat 44 dan Kitab Ta’lim Al-Muta’allim Karya Syaikh Az-Zarnuji) - Abdul Rouf; Moh. Irfan; Muhiddin Muhiddin (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2024)
This study aims to determine the Concept of Compassion and Advice in Seeking Knowledge (Analysis Study of QS. At-Thaha Verse 44 and the Book of Ta'lim Al-Muta'allim by Syaikh Az-Zarnuji). This study is a Library Research with a qualitative approach, taking the background of QS. Thaha Verse 44 and the Book of Ta'lim Al-Muta'allim by Az-Zarnuji. Data collection uses documentation methods in the form of books, scientific journals and e-books. While data analysis uses the inductive method. The results of the study show that: The concept of compassion and advice in seeking knowledge in QS. At-Thaha verse 44 from the perspective of Ibn Kathir's interpretation contains lessons and advice, which tells the story of Pharaoh at the peak of arrogance and pride, while the Prophet Moses was the chosen person of Allah SWT who was ordered not to speak to Pharaoh but to speak gently. In the Book of Talim Al-Muta'allim Imam Az-zarnuji conveys that a teacher must have a compassionate nature and always provide motivation in the form of advice to his students and a student must have good qualities far from bad qualities in seeking knowledge. Keywords: Compassion and Advice; Seeking Knowledge; Tafsir Ibn Kathir; Ta'lim Al-Muta'allim